NATIONAL PATRIOTIC EDUCATION IN THE STRUCTURE OF EXTRACURRICULAR EDUCATIONAL WORK OF THE SPECIAL SCHOOL - Одинченко, Лариса; Колот, Людмила (SWorldJournal, 2023)
The article reveals the relevance of the problem of national patriotic education of students with special educational needs in the context of Ukraine's full-scale war against the Russian aggressor. Attention is paid to the theoretical coverage of directi